The effect of chrome-cobalt and acrylic palatal plates on experimental denture stomatitis in Wistar rat - Kashmola, Muhanad Ali Hamdon; Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban (ELSEVIER, 2015)
Objective To compare effect of acrylic and chrome-cobalt on experimental oral candidiasis.